Magnificent leadership : transform uncertainty, transcend circumstance, claim the future - Levitt, Sarah (Human resource management and organizational behavior collection., 2018)
A must read for CEOs and senior business executives who wish to transform and transcend circumstance. Magnificent Leadership is the culmination of the author's interviews with leadership exemplars across all different domains for The Making Magnificence Project. Inviting you into the unique leadership journeys that she captured, the author distills the essential elements of leadership success gleaned during her interviews. Both senior leaders and the general population can use this book as a guide and resource for leading through uncertainty and living in aspiration. Although well suited for business executives leading in high stakes, chaotic environments, this book is for anyone who hopes to create something greater from circumstance and claim the future.